Mechnization to reduce human drudgery in coconut production - Mathew, A C; Manikantan, M R; Chowdappa, P (Indian Horticulture, 2018)
The greatest challenge coconut farmers are facing is climbing coconut tree for collecting tender nut, mature nuts and for other plant protection operations. Though the Joseph model of coconut climbing machine is gaining popularity, thanks to the initiative of Coconut Development Board (CDB), yet climbing the tree for harvesting would be prohibitively costly considering the stagnant price and productivity of coconut palm. Therefore, developing a mechanised device to harvest coconut from ground is the need of the hour. Invariably this should be focal point of researchers. Coconut de-shelling and de-husking are other two operations that require further mechanization. Though, a few prototypes of coconut de-shelling and de-husking machineries are either available or are in the pipeline, manual labour could not be avoided totally in these operations. There is a need for developing appropriate processing techniques and machinery suitable for community level processing of value added products like VCO, coconut chips, desiccated coconut, coconut milk, coconut milk powder etc.